THE UTILITY OF THE BARTER AGREEMENT IN INTERNATIONAL COMMERCIAL TRADE - OANA RĂVAŞ (Annals of the University of Petrosani: Economics)
This paper tries to explain how barter, as an economic institution, can help deal with the problem of contract enforcement across national borders in international trade and within borders in transition economies.